Promotion Of Women Rights In Gus Muhammad Iqdam Lecture Content At The Sabilut Taubah Forum On Social Media - Nimah, Zulfatun (UIN Sunan Kudus, 2024)
This paper aims to find out, explain and analyze the promotion ofwomen's rights for the general public by Gus Muhammad Iqdam as a religious figure who is intellectually not affiliated with the feminist Islamic scholarnetwork. Previous studies state that the promotion of women's rights has been widely carried out by feminist ulama by using reinterpretations of established religious texts, while non-feminist ulama tend to narrate women with gender-biased discourse so that women's rights are not fully understood by the public.This study uses a qualitative approach of the netnography type. Data is taken from the contents of Gus Iqdam's lectures on social media Tiktok, Instagram and Facebook. The results of the study show that through lectures at the Sabilu Taubah public religious study, Gus Iqdam has promoted several women's rights, including the right to enjoy equal status with her husband, the right to be treated well by her husband and the right to have her livelihood fulfilled, the right to be treated equally with male congregants in the religious study group, the right to lead the group and the right to use an identity according to their respective religions, where the promotion of these rights uses established classical terms; morals, blessings, birrul walidain (devotion to parents), and mu'asyarah bil ma'ruf (respecting the need and the willingness of the wife) which are not reinterpreted as new narratives formulated by feminist scholars, but are explained according to the context of the society that underlies their congregation.